2013
DOI: 10.3389/fphar.2013.00102
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic treatments; focus on lurasidone

Abstract: The introduction of atypical antipsychotic drugs (AAPDs), or second-generation antipsychotics, with clozapine as the prototype, has largely changed the clinicians' attitudes toward the treatment of mental illnesses including, but not limited to schizophrenia. Initially, there was optimism that AAPDs would be superior over typical antipsychotic drugs (TAPDs), or first-generation antipsychotic drugs, in terms of efficacy in various phenomenological aspects, including cognitive impairment, and less likelihood of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…In the present work, 0.5 mg/kg of flupenthixol produced a nonsignificant decrease in locomotor activity compared to the saline control group. The effect of these higher doses of flupenthixol on locomotor activity is not surprising as flupenthixol is a DAr antagonist and in humans, can induce extrapyramidal side effects (EPS) such as Parkinsonism, dystonia, and dyskinesia (Sumiyoshi, 2013). This is problematic and makes it difficult to differentiate a decrease in perseverative behavior from a sedative effect on movement.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, 0.5 mg/kg of flupenthixol produced a nonsignificant decrease in locomotor activity compared to the saline control group. The effect of these higher doses of flupenthixol on locomotor activity is not surprising as flupenthixol is a DAr antagonist and in humans, can induce extrapyramidal side effects (EPS) such as Parkinsonism, dystonia, and dyskinesia (Sumiyoshi, 2013). This is problematic and makes it difficult to differentiate a decrease in perseverative behavior from a sedative effect on movement.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that no data were presented in that study (Goldberg et al 2007) as to whether schizophrenia patients not receiving AAPDs would have elicited the same degree of improvement as that in treated patients. In fact, lurasidone, an AAPD with high affinity for 5-HT 1A receptors, has been reported to dose-dependently improve cognitive function in a placebo-controlled double-blind study (Harvey et al 2013;Sumiyoshi 2013).…”
Section: Pharmacological Treatments Of Cismentioning
confidence: 99%
“…It is reported that adjunctive treatment with selective 5-HT 1A receptor (partial) agonists, e.g., tandospirone or buspirone, was associated with improvements in some types of cognitive function in patients with schizophrenia (Sumiyoshi et al, 2001b , 2007 ; Sumiyoshi and Higuchi, 2013 ). These observations provide the basis for the ability of 5-HT 1A receptor stimulation to enhance cognition, a therapeutic approach that have promoted the development of novel antipsychotic drugs (Sumiyoshi, 2013 ; Sumiyoshi et al, 2013 ).…”
Section: Introductionmentioning
confidence: 96%